2006
DOI: 10.1590/s0100-879x2006000800017
|View full text |Cite
|
Sign up to set email alerts
|

Obese obstructive sleep apnea patients with tonsil hypertrophy submitted to tonsillectomy

Abstract: The physiopathology of obstructive sleep apnea-hypopnea syndrome (OSAHS) is multifactorial and obesity has been shown to be one of the main factors correlated with its occurrence. In obese patients with anatomical alterations of the upper airways it is often difficult to predict success for surgical correction since obesity is a limiting factor. Therefore, the aim of the present study was to evaluate the results of tonsillectomy in a specific group of patients, i.e., obese OSAHS patients with tonsil hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…67,68 Studies were excluded for the following reasons: only posttonsillectomy data was available, 24 no polysomnography or quantitative sleepiness data, 20,29,34,38,44,48,56,57,[60][61][62]64,65 the patient(s) underwent a tonsillectomy alone; however, the studies only reported data for the entire group which included additional surgeries, 28,41,[50][51][52][53] the patient(s) underwent another procedure simultaneously, 10,22,27,42,45,46,55,58,67,69 or the articles were review articles with no new data. 23,30 Seventeen studies 21,25,26,[31][32][33][35][36][37]39,40,42,49,54,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Studies were excluded for the following reasons: only posttonsillectomy data was available, 24 no polysomnography or quantitative sleepiness data, 20,29,34,38,44,48,56,57,[60][61][62]64,65 the patient(s) underwent a tonsillectomy alone; however, the studies only reported data for the entire group which included additional surgeries, 28,41,[50][51][52][53] the patient(s) underwent another procedure simultaneously, 10,22,27,42,45,46,55,58,67,69 or the articles were review articles with no new data. 23,30 Seventeen studies 21,25,26,[31][32][33][35][36][37]39,40,42,49,54,…”
Section: Resultsmentioning
confidence: 99%
“…The study by Senchak et al was a prospective case‐control study with mostly young subjects (mean age 28 years) with mild or moderate OSA. Chen et al and Miyazaki et al had patients with a lower BMI (mean < 25 kg/m 2 ), whereas the patients in the studies by Houghton et al and Martinho et al had a higher overall BMI (33.3 kg/m 2 and 36.6 kg/m 2 , respectively). An additional variable that likely contributed to the overall heterogeneity includes the fact that only studies by Chen et al and Senchak et al were performed at multiple institutions, whereas the remaining studies were performed at single institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in respiratory parameters, there was evidence of residual sleep disordered breathing in most reports. More recent trials by MARTINHO et al [186] and NAKATA et al [187] investigated patients with OSA who where either intolerant to a CPAP trial or required high CPAP pressures to treat upper airway obstruction due to tonsillar hypertrophy. Based on these reports tonsillectomy play a role similar to nasal surgery in increasing the use of CPAP in patients with tonsillar hypertrophy, or when CPAP therapy is not possible as the first choice of therapy.…”
Section: Search Criteriamentioning
confidence: 99%
“…A small number of studies have explored the role of tonsillectomy in selected adult cases, after unsuccessful CPAP treatment. [3][4][5] Success has been in the range of 40% to 100%, but subject numbers have been small. We present our experience with tonsillectomy and nasal surgery for OSA in selected adult subjects.…”
mentioning
confidence: 99%